2020
DOI: 10.3329/jdmc.v27i2.45827
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglycerides and Total Cholesterol levels and its Relation with type 2 148 Diabetes mellitus

Abstract: Diabetes mellitus is one of the most widespread endocrine disorder in female and its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and end stage renal diseases. A relation between hyperlipidemia and diabetes mellitus has been identified. The study was carried out to observe the serum triglycerides and total cholesterol levels its relation with type 2 diabetes mellitus in adult female subjects. This cross sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Both hyperglycemia and hyperinsulinemia aggravate IR and stimulate hepatic lipogenesis [ 26 ]. A recent study demonstrated that an increase in serum insulin and glucose levels may underpin elevated serum TG and cholesterol levels [ 27 ]. Collectively, these data demonstrate that an increase in serum glucose and insulin levels elevate lipogenic gene expression and serum lipid levels, indicating an increased risk of developing T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperglycemia and hyperinsulinemia aggravate IR and stimulate hepatic lipogenesis [ 26 ]. A recent study demonstrated that an increase in serum insulin and glucose levels may underpin elevated serum TG and cholesterol levels [ 27 ]. Collectively, these data demonstrate that an increase in serum glucose and insulin levels elevate lipogenic gene expression and serum lipid levels, indicating an increased risk of developing T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The well pronounced hypertriacylglyceridaemia on the 5th and 10th day in experimental rats is accompanied by hypercholesterolemia and an increase in VLDL and LDL ( Table 3 ). Changes in the lipid profile, according to Schenk et al [ 55 ] and Yeasmin et al [ 56 ], are associated with an impaired ability of insulin to inhibit hormone-sensitive lipase and an increase in serum concentrations of free fatty acids. High levels of free fatty acids induce insulin resistance in adipose tissue and skeletal muscle [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is also linked to T2D as both insulin shortage and insulin resistance lead to impaired lipid metabolic pathways [12]. Changes in total cholesterol are associated with an increased risk of developing T2D, regardless of whether or not anti-hyperlipidemic medications are used [13]. Research suggests that lower levels of adiponectin are linked to insulin resistance, which influences the development of hyperlipidemia in T2D, and adiponectin is positively linked to triglycerides [14].…”
Section: Introductionmentioning
confidence: 99%